Проект поводження з відходами буріння: на прикладі Вигодо – Витвицького родовища - Babiak, Khrystyna (My University, 2014)
Aim of project: to develop a method for the treatment of drilling waste. Results: that the optimal method of treatment of drilling waste a method of forest recultivation of slime barns is. Recommended use: ?pply a combined method of remediation of sludge barns ensures their actual restoration by maximizing the potential of using natural remediation and improve the aesthetic appearance of the area. Economic and ecological efficiency: a method for forest recultivation of sludge barns are economically expedient because they do not require large expenditures, environmentally effective this method is the fact that neutralizes dangerous substances contained in the composition of drilling muds and drilling waste water, improves nakolyshnoho environment by greenery.

Cel: opracowanie sposobu obróbki odpadów wiercenia. Wyniki: badania, że najlepszą metodą przetwarzania odpadów wiercenia jest metoda rekultywacji lasów stodołach zawiesiny. Zalecane użycie: Nanieść połączoną metodę rekultywacji stodołach osadów zapewnia ich rzeczywiste odtworzenie poprzez maksymalizację potencjału przy użyciu naturalnego rekultywację i poprawę wyglądu estetycznego terenu. Efektywności ekonomicznej i środowiskowej: metoda rekultywacji stodołach osadów są opłacalne, ponieważ nie wymaga dużych nakładów, efektywne dla środowiska metoda ta jest fakt, że neutralizuje substancje niebezpieczne znajdujące się w składzie płuczek wiertniczych i ścieków wiercenie, poprawia nakolyshnoho otoczenie zieleni.

Мета проекту: розробка схеми поводження з буровими відходами для умов даного родовища. Результати: досліджено, що оптимальним методом поводження з буровими відходами є комбінований метод рекультивації шламового амбару. Рекомендації щодо використання: застосування комбінованого способу рекультивації шламових амбарів дозволяє забезпечити їх реальну рекультивацію за рахунок максимального використання потенційних можливостей природної рекультивації і покращить естетичний вигляд території. Економічна та екологічна ефективність: метод рекультивації для шламових амбарів, є економічно доцільним, так як не вимагає великих затрат; екологічно ефективний цей метод є тому, що знешкоджує небезпечні речовини, які містяться в складі бурових шламів та бурових стічних вод, покращує стан наколишнього середовища за рахунок зелених насаджень.
The project of drilling waste treatment in the area of the Vygoda-Vytvytsk field
Projekt zagospodarowania odpadów wiertniczych na terenie zloża Wyhodo-Wytwyckiego
prezentacja pracy dyplomowej
streszczenia
Keywords: odpady; ścinki wiercenia; wiercenie ścieków; stodoła; metody rekultywacji osadów; odtworzenie lasów; waste drilling cuttings; drilling wastewater; sludge barn; methods recultivation; forest recultivation